Dual career pathways: Psychological and environmental determinants of professional athletes` development - Siekanska, M.; Blecharz, J. (Studies in Sport Humanities, 2014)
The purpose of the study was: (a) to determine the process of dual career development (e.g., stages of develop- ment, turning points) and its relationship with the type of dual career pathway; (b) to investigate the relation- ships between some psychological determinants and the type of dual career pathway; (c) to investigate the relationships between environmental determinants and the type of dual career pathway; (d) to examine the relationships between the type of dual career development and the quality of life. Data was collected using a semi-structured interview, The General Self-Efficacy Scale (GSES), The Satisfaction with Life Scale (SWLS). Athletes (N = 95) were divided into three subgroups representing three types of dual career pathways: 1) Balanced and harmonious development - no conflict between sport and education per- ceived (N = 40); 2) Unbalanced development - orientation to sport development (at the cost of educational development) (N = 34); 3) Unbalanced development - orientation to educational development (at the cost of sport development) (N = 21). The ANOVA analysis and chi2 test yielded 19 statistically significant differences between the groups of dual ca- reer pathways as regards: athletes` family situation, the process of their development, self-efficacy, and the qual- ity of life.